Acer infesting aphids (Hemiptera: Aphididae) of the Himalaya with description of a new species of Trichaitophorus Takahashi from Bhutan. (2nd January 2019) - Chakrabarti, S.; Das, D.; Sarkar, S.
Abstract: A new species, Trichaitophorus acerifolius sp. nov. infesting Acer sp. in Bhutan is described. A key to 15 species infesting different species of Acer in the Himalaya is provided. http://www.zoobank.org/urn:Isid:zoobank.org:act:C1E4EFED-70F6-4E6D-844F-2BE62EB741F5